LARGE DEBRIS AVALANCHES AND ASSOCIATED ERUPTIONS IN THE HOLOCENE ERUPTIVE HISTORY OF SHIVELUCH VOLCANO, KAMCHATKA, RUSSIA - Ponomareva V.V.; Melekestsev I.V.; Pevzner M.M. (My University, 1998)
Shiveluch Volcano, located in the Central Kamchatka Depression, has experienced multiple flank failures during its lifetime, most recently in 1964. The overlapping deposits of at least 13 large Holocene debris avalanches cover an area of approximately 200 km2 of the southern sector of the volcano. Deposits of two debris avalanches associated with flank extrusive domes are, in addition, located on its western slope. The maximum travel distance of individual Holocene avalanches exceeds 20 km, and their volumes reach ∼3 km3. The deposits of most avalanches typically have a hummocky surface, are poorly sorted and graded, and contain angular heterogeneous rock fragments of various sizes surrounded by coarse to fine matrix. The deposits differ in color, indicating different sources on the edifice. Tephrochronological and radiocarbon dating of the avalanches shows that the first large Holocene avalanches were emplaced approximately 4530–4350 BC. From ∼2490 BC at least 13 avalanches occurred after intervals of 30–900 years. Six large avalanches were emplaced between 120 and 970 AD, with recurrence intervals of 30–340 years. All the debris avalanches were followed by eruptions that produced various types of pyroclastic deposits. Features of some surge deposits suggest that they might have originated as a result of directed blasts triggered by rockslides. Most avalanche deposits are composed of fresh andesitic rocks of extrusive domes, so the avalanches might have resulted from the high magma supply rate and the repetitive formation of the domes. No trace of the 1854 summit failure mentioned in historical records has been found beyond 8 km from the crater; perhaps witnesses exaggerated or misinterpreted the events.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен